Mitochondrial uncoupler DNP induces coexistence of dual-state hyper-energy metabolism leading to tumor growth advantage in human glioma xenografts - Rai, Yogesh; Singh, Saurabh; Pandey, Sanjay; Sah, Dhananjay; Sah, Raj Kumar; Roy, B. G.; Dwarakanath, Bilikere S.; Bhatt, Anant Narayan (Frontiers in Oncology, 2022)
Cancer bioenergetics is an essential hallmark of neoplastic transformation. Warburg postulated that mitochondrial OXPHOS is impaired in cancer cells, leading to aerobic glycolysis as the primary metabolic pathway. However, recent studies confirmed that mitochondrial function is changed but not entirely compromised in most malignancies. Mitochondrial uncoupling is known to increase the carcinogenic potential and modifies the treatment response by altering metabolic reprogramming. Here, we utilized 2,4-dinitrophenol (DNP), a mitochondrial uncoupler, in human glioma cells (BMG-1) to understand the significance of energy metabolism in tumor development. Our earlier study reported that transient DNP exposure increases glycolysis in BMG-1 cells. The present study aimed to investigate the persistent effect of DNP on the energy metabolism of BMG-1 cells and its influence on tumor progression in glioma xenografts. Our preliminary in-vitro analysis revealed that chronic exposure to DNP for mild uncoupling in BMG-1 leads to a dual-state hyper-energy metabolism characterized by elevated levels of both aerobic glycolysis++ and OXPHOS++ compared to parental BMG-1 cells with relatively low glycolysis+ and OXPHOS+. Tumor xenograft of OPM-BMG cells showed relatively increased tumor-forming potential and accelerated tumor growth in nude mice. Moreover, compared to BMG-1, OPM-BMG tumor-derived cells also showed enhanced migration and invasion potential. These results suggest that dual-state hyper-energy metabolism provides a competitive tumor growth advantage over the existing glioma phenotype. Although mitochondrial uncouplers are proposed as a valuable anti-cancer strategy; however, our findings reveal that prolonged exposure to uncouplers like DNP results in dual-state hyper-energy metabolism and may lead to poor clinical outcomes.